Simulation and Optimization of Thermosyphon Solar WateHeater for Kuala Lumpur Climate Using Trnsys Software - Zahedi, Seyed Hamidreza (2005)
Solar energy can be utilized for hot water supply in Malaysia but demand is at night and in the early morning. Auxiliary heater can help reduce this mismatch. The objective of this project is to develop a transient simulation program (TRNSYS) by set the system using suitable parameters for Kuala Lumpur, to determine the optimal system design and the system performance during the year for 150literfday hot water consumption for five persons. TRNSYS is a transient system simulation program which is use for thermal analysis of a variety of time dependent systems. The modular nature of TRNSYS permits simulation of a great variety of particular components of a physical system and facilitates the add ons to the program of mathematical model which is not included in standard TRNSYS library. A typical thermosyphon solar domestic hot water (DHW) system can be modeled by connecting thermosyphon collector storage subsystem (Type 49, Typical Meteorological Year (TMY) weather data reader (Type89), radiation processor (Type 16), heating load component (Type 14), integrator (Type 24) and online plotter (Type65). It was observed that the collector should be tilted at @+(7" + 37")which is faced to south, according to Kuala Lumpur latitude (e3.14q.In terms of storage tanks configuration the vertical system has better performance rather than horizontal one. The optimal system designs are: Nr=lO, D, =5 mm, Do, Di=15mm, H, when the Ht is lm2 should be more than 0.8m and the optimum tank height is about lm. In case of tank volume it is highly depend on the set point (hot water temperature to load), but for most of the cases is between 125-150 liter. The optimum collector area for 150 litertday consumption is about 2m2; there is no effect in increasing the collector area. It is concluded that the system without auxiliary water heater can not reach the requirements, if the set point is 55°C. In most of the month of the year the mean monthly water temperature is more than 50°C. The auxiliary is needed for cooler months like June, July and November. The auxiliary heating consumption in solar system is about 90% less than the geyser (see Figure5.19).